Nonpharmacological Interventions for Preventing Rehospitalization Among Patients with Heart Failure: A Systematic Review and Meta-Analysis - Nader Alnomasy; Carolyn Harmon Still (SAGE Publishing, 2023)
Background Heart failure (HF) is the most common condition for rehospitalization among people aged ≥65 years in the United States, with 35,197,725 hospitalizations between 2014 and 2017. Hospitalized patients with HF have the highest 30-day readmission rate (25%). Overall, HF management, despite its progress, remains a challenge. Although several studies have evaluated interventions designed to reduce HF-related hospital readmissions, research comparing their effectiveness remains insufficient. Purpose This systematic review and meta-analysis focused on studies that investigated the effectiveness of nonpharmacological interventions (NPIs) on reducing rehospitalization among patients with HF. Methods This review conformed to the preferred reporting items for systematic reviews and meta-analyses guidelines, used four databases: Cumulative index to Nursing and Allied Health Literature, PubMed, Cochrane, and Web of Science. Studies were included in the review according to the following criteria: (a) included only randomized control trials (RCTs), (b) included participants with HF who were over 18 years of age, (c) peer-reviewed, (d) written in English, and (e) rehospitalizations occurring within 30-day, 90-day, and 1 year of discharge from the initial hospitalization. Results Fourteen studies were included, with a total of 2,035 participants. Meta-analysis showed that rehospitalization was different between the intervention and usual care groups. The odds ratio was 0.54 (95% confidence interval [0.36, 0.82, p  < 0.01]). Conclusions/Implications for Practice NPIs designed to increase HF knowledge and self-management may effectively reduce rehospitalization among HF patients. NPIs can be delivered at the patient's home through visits, phone calls, or digital platforms and technologies.